ANALISIS SEAKEEPING PADA PENAMBAHAN STERN WEDGE DENGAN VARIASI SUDUT DAN GELOMBANG KAPAL BERJENIS MONOHULL - Raden Roro Andhika Dharmaura Indriastuti, (2023)
The ability of the ship's motion to survive on the waves or known as seakeeping is influenced by several external factors related to the ship's sea conditions and the waters in which the ship sails. Seakeeping on a ship is the ability of a ship to stay afloat in any condition related to the ship's floating structure such as waves and weather. Stern Wedge is a modification of the ship's shape at the stern of the ship's hull, precisely below the stern. Variation of stern wedge angle 4°,6°,8°,10°, variation of wave angle 45°, 90°, 180°. At a speed of 2m/s compared to an angle of 0° at an angle of stern wedge 4°, 6°, and 10° it is effective to add a stern wedge because it obtains a low frequency of 0.194 rad/s at an angle of 45° with the heave ship movement. Then at speed of 4m/s there is a stern wedge angle of 4° with a frequency of 0.188 rad/s, and a stern wedge of 6° with a frequency of 0.194 rad/s with a wave angle of 45°, it is effective to add the stern wedge to that angle. For a speed of 6m/s, the stern wedge angle is 4° with 0.183 rad/s heave movement and 0.183 rad/s pitch movement, then at a stern wedge angle of 6°, 0.183 rad/s heave movement is obtained. So for roll, pitch, heave that looks low on the graph, the angle of the ship's motion is lower than the motion of the ship with a high value on the graph.